Mitologia conceitual: sacralidade na arte conceitual da década de 1960 - Lucas Carvalho Rola Santos (2013)
This Dissertation aims to elaborate on possible relations that can be establish between practices and precepts of the Conceptual Art of the 1960s and the Sacredness. Although regarded as a much rational chain of contemporary art, the Conceptual Art is surrounded by a mysticalcondition, which, though rarely theoretically approached by the conceptual artists, came to be directly explained by Sol LeWitt, to whom "Conceptual artists are mystics rather than rationalists. They leap to conclusions that logic cannot reach" (LEWITT, Sol apud FERREIRA, Gloria; COTRIM , Cecilia, 2006, p. 205). On that line, this work aims to provide a theoreticalmaterial, bringing new forms of approach and critical interpretation about issues and the production dynamics of Conceptual Art. In order to do so, the analysis employed emblematic works of Conceptual Art and texts of the great literature produced by the conceptual artists in the 1960s (which, besides being theoretical postulates, can be understood as works of art as well), with special attention to texts from Joseph Kosuth, great theoretical exponent and artist of Conceptual Art, as well as texts from Sol LeWitt, Mel Bochner and the Art & Language group.